Electronic Structure of Various Shapes of Graphene Quantum Dot - Ramli, Irwan; N. Sani; Sukarti; Nurmalasari (BRIN Publishing (Penerbit BRIN), 2025)
– We reported our study the electronic structure of graphene in bulk structure and graphene quantum dot (GQD) by density functional theory (DFT) by using in quantum espresso (QE) package. In order simulate the realistic shape of GQD, we set vacuum layer to avoid interaction between quantum dot in the periodic structure in crystal. We examined various shape of quantum dot namely triangular, Hexagon, parallelogram. The band gap is tunable by its shape which open wide application of GQD. We showed that we can tuning the electronic structure of graphene by tuning its structure. In bulk structure, graphene is zero-gap semiconductor. On the other hand, the results on GQD showed the discrete energy level and different shapes of GQD have different energy level and band gap.